Description of two new species of apple snail (Ampullariidae: Pomacea) from Peruvian Amazonia - Ampuero, André; Ramírez, Rina (Zootaxa, 2023)
Two new species of apple snails are described, Pomacea penai sp. nov. and Pomacea reevei sp. nov. that are used as food resources in Peruvian Amazonia. We used anatomical and conchological features to diagnose these two species. Pomacea penai sp. nov. is characterized by a highly variable shell morphology, spire that is prominent to immersed, apical penis sheath gland covering 1/3 penis sheath and elongated basal gland, prostate broad proximally, reduced stomach septum, green eggs, and commonly inhabits temporary flooded areas, creeks, and oxbow lakes. Pomacea reevei sp. nov. possesses a large shell, ranging from 81–137 mm, grey broad penis sheath, small apical penis sheath gland and the basal gland covering 1/3 penis sheath, tall stomach septum, white eggs, and found in deep lentic water bodies.